2017
DOI: 10.3238/arztebl.2017.0665
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mental Illness in Homeless People in Germany

Abstract: In Germany, the rate of mental illness requiring treatment is higher among the homeless than in the general population. The development and implementation of suitable care models for this marginalized and vulnerable group is essential if their elevated morbidity and mortality are to be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 51 publications
7
74
0
20
Order By: Relevance
“…At the end of this stage, we removed 826 citations due to non-compliance with our criteria and evaluated full texts of the remaining 22 citations. Seven articles were excluded at this stage, and we retained 15 articles in this review (Ayano, Tesfaw, & Shumet, 2019;Ayano, Tsegay, Abraha, & Yohannes, 2019;Bassuk, Richard, & Tsertsvadze, 2015;Burra, Stergiopoulos, & Rourke, 2009;Depp, Vella, Orff, & Twamley, 2015;Duke & Searby, 2019;Embleton, Mwangi, Vreeman, Ayuku, & Braitstein, 2013;Ennis, Roy, & Topolovec-Vranic, 2015;Fazel, Khosla, Doll, & Geddes, 2008;Folsom & Jeste, 2002;Hodgson, Shelton, van den Bree, & Los, 2013;Parks, Stevens, & Spence, 2007;Schreiter et al, 2017;Smartt et al, 2019;Spence, Stevens, & Parks, 2004). The included articles consisted of seven meta-analytic reviews (Ayano, Tesfaw, et al, 2019;Ayano, Tsegay, et al, 2019;Bassuk et al, 2015;Depp et al, 2015;Embleton et al, 2013;Fazel et al, 2008;Schreiter et al, 2017), and eight non-quantitative reviews (Burra et al, 2009;Duke & Searby, 2019;Ennis et al, 2015;Folsom & Jeste, 2002;Hodgson et al, 2013;Parks et al, 2007;Smartt et al, 2019;Spence et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the end of this stage, we removed 826 citations due to non-compliance with our criteria and evaluated full texts of the remaining 22 citations. Seven articles were excluded at this stage, and we retained 15 articles in this review (Ayano, Tesfaw, & Shumet, 2019;Ayano, Tsegay, Abraha, & Yohannes, 2019;Bassuk, Richard, & Tsertsvadze, 2015;Burra, Stergiopoulos, & Rourke, 2009;Depp, Vella, Orff, & Twamley, 2015;Duke & Searby, 2019;Embleton, Mwangi, Vreeman, Ayuku, & Braitstein, 2013;Ennis, Roy, & Topolovec-Vranic, 2015;Fazel, Khosla, Doll, & Geddes, 2008;Folsom & Jeste, 2002;Hodgson, Shelton, van den Bree, & Los, 2013;Parks, Stevens, & Spence, 2007;Schreiter et al, 2017;Smartt et al, 2019;Spence, Stevens, & Parks, 2004). The included articles consisted of seven meta-analytic reviews (Ayano, Tesfaw, et al, 2019;Ayano, Tsegay, et al, 2019;Bassuk et al, 2015;Depp et al, 2015;Embleton et al, 2013;Fazel et al, 2008;Schreiter et al, 2017), and eight non-quantitative reviews (Burra et al, 2009;Duke & Searby, 2019;Ennis et al, 2015;Folsom & Jeste, 2002;Hodgson et al, 2013;Parks et al, 2007;Smartt et al, 2019;Spence et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Most reviews (n = 10) included primary studies from multiple countries without specific geographic or economic focus, whereas three reviews emphasized on high-income countries (Bassuk et al, 2015;Fazel et al, 2008;Schreiter et al, 2017) and two reviews included studies from LMICs or resource-constrained contexts (Embleton et al, 2013;Smartt et al, 2019).…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stefanie Schreiter et al found on the basis of their systematic review that the prevalence of mental disorders is notably higher in homeless people than in the general population (1). In homeless people, the prevalence of substance misuse related disorders is 60.9%-which is 21 times the rate seen in the general population.…”
Section: Difficulty In Accessing Servicesmentioning
confidence: 99%